Modelling wave group-scale hydrodynamics on orthogonal unstructured meshes. (April 2023) - Reyns, Johan; McCall, Robert; Ranasinghe, Roshanka; van Dongeren, Ap; Roelvink, Dano
Abstract: An unstructured hydrodynamic model is presented that is able to simulate 2D nearshore hydrodynamics on the wave group scale. A non-stationary wave driver with directional spreading, with physics similar to XBeach (Roelvink et al., 2009) is linked to an improved and extended version of the existing unstructured flow solver Delft3D–FM (Kernkamp et al., 2011; Martyr-Koller et al., 2017). The model equations are discretised on meshes consisting of triangular and rectangular elements. The model allows for coverage of the model domain with locally optimised resolution to accurately resolve the dominant processes, yet with a smaller total number of grid cells. The model also allows a larger explicit time step, compared to structured models with similar functionality. The model reliably reproduces measured datasets of water levels, sea/swell and low frequency wave heights in laboratory and field conditions, and is as such widely deployable in a variety of simple and complex coastal settings to study nearshore hydrodynamics. Highlights: We present an unstructured model for wave group time scale hydrodynamics. Computational cost decreases for many practical applications. The model was assessed against laboratory and field datasets. The source code is open source as part of Delft3D.